Osteomyelitis due to arsenic trioxide use for tooth devitalization - DUMLU, ASIM; ERÇALIK YALÇINKAYA, ŞEBNEM (WILEY, 2007)
Aim To present a case of osteomyelitis that was caused by the use of arsenic trioxide during root canal treatment in a mandibular left first molar. Summary Arsenic was once in common use to devitalize inflammed pulp tissue before root canal treatment. Its prolonged application or leakage leads to toxic effects beyond the pulp tissue, and necrosis of periodontal tissues and supporting alveolar bone has been described. This report presents a case of osteomyelitis resulting from leakage of arsenic trioxide used in pulp devitalization. Sequestrectomy and excision of non-vital alveolar bone was performed to treat the severe tissue necrosis. Key learning points Agents containing arsenic are still employed by some clinicians and may be encountered when patients present with tissue destruction resulting from their use. Dental practitioners should be aware that arsenic paste may diffuse into periodontal tissues through apical, lateral or accessory canals, through perforations and around leaking restorations. Osteomyelitis caused by arsenic trioxide can be treated by a combination of pharmacotherapeutic and invasive surgical methods. Arsenic pastes have no place in endodontic practice.
Keywords: arsenic trioxide; osteomyelitis; sequestrectomy; NECROSIS